Combined effects of arginine and hydroxyurea on BFU-E derived colony growth and HbF synthesis in erythroid progenitors isolated from sickle cell blood - Baliga, B. S.; Haynes Jr, J.; Obiako, B.; Mishra, N. (Cellular and Molecular Biology, 2010)
Hydroxyurea (HU) increases HbF synthesis in sickle cell disease (SCD). Recent studies suggest HU-induced HbF synthesis is mediated through a NO-cGMP pathway. Since arginine is the main precursor of NO, we investigated the effects of arginine and HU mixtures on HbF synthesis and burst forming unit erythroid (BFU-E) proliferation. Mixtures of HU (0, 15, 25, 100µM) and arginine (0, 25, 50, and 100µM) resulting in optimal HbF synthesis and minimal HU-induced cytotoxicity in erythroid progenitors were determined. HU dose-dependently attenuated growth of BFU-E colonies and stimulated HbF synthesis. In contrast, arginine dose-dependently increased BFU-E colonies without affecting HbF synthesis. Furthermore, arginine at concentrations >100µM in combination with varying concentrations of HU, decreased HbF synthesis compared to HU controls. HU, 15-25µM, in combination with 25-50µM arginine not only minimized cytotoxicity, but also increased HbF synthesis when compared with HU controls. NG-nitro-L-arginine-methyl ester (L-NAME; 100µM), a nitric oxide synthase inhibitor, attenuated the effects of HU+arginine on HbF synthesis compared to HU and HU+arginine controls. These results suggest HU+arginine-induced HbF synthesis in human erythroid progenitors is NO dependent. The synergistic effect on HbF synthesis seen with combinations HU+arginine is an important observation in understanding potential therapeutic uses of HU and arginine.